INTERNATIONAL LEGAL COOPERATION AND THE PRINCIPLE OF PUBLIC POLICY: LESSONS FROM INTELLECTUAL PROPERTY LAW - DOI 10.5935/2448-0517.20200029 - Naim, Nadia (Juris Poiesis - Qualis A3, 2020)
This research paper will examine the different approaches to corporate legal theory in the international legal co-operation of International Intellectual Property (IP). The focus will be on legal cooperation as a means to promoting harmonisation in line with international standard setting from the World Intellectual Property Office (WIPO) and the World Trade Organisation (WTO). Harmonisation can be seen through the minimum standards set through WIPO for all WTO members known as Trade Related Intellectual Property Rights (TRIPS). The landmark cases of Philip Morris v. The Commonwealth of Australia and Eli Lilly v Canada will be discussed as a case study to highlight the lack of harmonisation between Intellectual Property, corporate sovereignty and Investor to State Dispute Settlements (ISDS). This abstract presents the initial hypotheses and some primary conclusions from the research.